Land Bank Agency in The Implementation of Land Acquisition for the Public Interest in Indonesia - Irman Syahriar; Benhard Kurniawan Pasaribu; Dina Paramitha Hefni Putri; Khairunnisah Khairunnisah (Journal of Social Research, 2022)
Background: Land acquisition is a way to acquire land for development for the public good. Article 18 of the Agrarian Constitution number 5 of 1960 states that: "for the public interest, including also for the benefit of the nation and the state as well as the common interests of the people, the right to land can be revoked, by providing appropriate compensation and by the manner regulated by the Law, then judging from the principle of land rights that has been stated in Article 6, namely land has a social function. Objective: The government initiated the concept of Land Banking which aims to record, collect, and distribute land that is appropriate to its circumstances and nature and can be included in the Land Bank. Methods: Research methods use normative legal research methods. The establishment of the Land Bank is inseparable from the efforts of the government which seeks to provide land for development and the public interest so that the land is not controlled by the land mafia that afflicts the people. Result: A supporting legal tool that can be in the form of a law that specifically regulates land banks, then the implementation of land banks in Indonesia will run according to their functions appropriately and effectively to obtain large results. This condition will improve the welfare of each individual and society in general and by the mandate of the constitution which aims to realize the greatest prosperity of the Indonesian people. Conclusion: Full management of land assets that have been controlled and aimed at realizing an equitable economy is the authority of the land bank. Government asset land is different from state land, government asset land is land controlled by Government agencies, both central and local governments. Currently, there is an area of 25,000 ha of land that has been determined to be the initial capital of the Land Bank and has been prepared by the Ministry of Agrarian and Spatial Planning / National Land Agency (ATR / BPN).